2006
DOI: 10.1021/nl052130h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Gold Micro- and Nanostructures by Photolithographic Exposure of Thiol-Stabilized Gold Nanoparticles

Abstract: Exposure of thiol-stabilized gold nanoparticles supported on silicon wafers to UV light leads to oxidation of the thiol molecules and coagulation of the nanoparticles, forming densified structures that are resistant to removal by solvent exposure. Unoxidized particles may, in contrast, readily be removed leaving gold structures behind at the surface. This process provides a convenient and simple route for the fabrication of gold structures with dimensions ranging from micrometers to nanometers. The use of mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…These may be formed into bilayers on silicon surfaces using Langmuir-Schaeffer techniques [87]. It has been found that selective exposure of the nanoparticles to UV light causes them to fuse together [88]. In a very simple second step, the sample may merely be rinsed with toluene; the unexposed nanoparticles are washed away, leaving intact structures behind.…”
Section: Uv Rch 3 Rcoohmentioning
confidence: 99%
“…These may be formed into bilayers on silicon surfaces using Langmuir-Schaeffer techniques [87]. It has been found that selective exposure of the nanoparticles to UV light causes them to fuse together [88]. In a very simple second step, the sample may merely be rinsed with toluene; the unexposed nanoparticles are washed away, leaving intact structures behind.…”
Section: Uv Rch 3 Rcoohmentioning
confidence: 99%
“…One method to create these patterns is by exposure of thiol-stabilised gold NPs supported on silicon wafers to UV light leading to oxidation of the thiol and coagulation of the NPs [20], or photo-crosslinking of C60 derivatives [21], forming dense structures that are resistant to removal by organic solvents. Methods exist to further derivatise gold surfaces, such as those formed, with oligonucleotide sequences [11,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] For the catalysis, the oxidation on the materials by light generates electron-transfer processes that may be used for the degradation of the organic pollutants. 7 Activity and selectivity of such materials and catalysts is correlated with the distribution.…”
Section: Introductionmentioning
confidence: 99%